THE EFFECT OF CASH CONVERSION CYCLE ON THE PROFITABILITY OF THE RETAIL TRADE SECTOR COMPANIES - Mandalaputri, Renata; Fettry, Sylvia; Felisia, Felisia (Kesatuan Press, 2021)
One of the company's goals is to increase company value. In order to achieve these goals the company must increase its profitability. To increase profitability, companies have to manage working capital effectively and efficiently. The effectiveness of working capital management can be measured using the Cash Conversion Cycle (CCC). CCC consists of Days Sales Outstanding (DSO), Days Sales Inventory (DSI), and Days Payable Outstanding (DPO). This study aims to determine the effect of the CCC and its components on company profitability. The type of data used in this study is secondary data which are collected from of corporate financial reports. The population in this study are retail trading companies listed on the Indonesia Stock Exchange during the 2015-2019 period. The data analysis method used in this study is the multiple linear regression method for panel data and simple linear regression for panel data. The results showed that partially, DSO, DSI, and CCC had a negative effect on company profitability. Meanwhile, the DPO has a positive effect on company profitability. Simultaneously, DSO, DSI, and DPO have an effect on profitability. Therefore, companies need to pay attention to the CCC and its components (DSO, DSI, and DPO) and manage it properly.